What is the impact of artificial intelligence-based chatbots on infodemic management? - Morita, Plinio P.; Lotto, Matheus; Kaur, Jasleen; Chumachenko, Dmytro; Oetomo, Arlene; Espiritu, Kristopher Dylan; Hussain, Irfhana Zakir (Frontiers in Public Health, 2024)
Artificial intelligence (AI) chatbots have the potential to revolutionize online health informationseeking behavior by delivering up-to-date information on a wide range of health topics. They generate personalized responses to user queries through their ability to process extensive amounts of text, analyze trends, and generate natural language responses. Chatbots can manage infodemic by debunking online health misinformation on a large scale. Nevertheless, system accuracy remains technically challenging. Chatbots require training on diverse and representative datasets, security to protect against malicious actors, and updates to keep up-to-date on scientific progress. Therefore, although AI chatbots hold significant potential in assisting infodemic management, it is essential to approach their outputs with caution due to their current limitations.